2019
DOI: 10.1088/1361-6641/ab1105
|View full text |Cite
|
Sign up to set email alerts
|

Trap state characterization of Al2O3/AlInGaN/GaN metal-insulator-semiconductor heterostructures

Abstract: Frequency-dependent conductance measurements were carried out to investigate the trap states in Al 2 O 3 /AlInGaN/GaN metal-insulator-semiconductor (MIS) heterostructures. From the electrical measurements, an improvement in trap state characteristics was observed for the device fabricated with lower In composition in quaternary nitride layers. In the presence of higher In composition, segregation of In atoms was observed in AlInGaN layers. Because of this Insegregation, surface quality of the quaternary-N dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[29] And its value of 2 × 10 12 cm −2 is employed in this work. [30,31] Conversely, the electron accumulation region is formed near the trench surface due to the positive Q f at the SiO 2 /GaN interface, which is the main factor of increasing the surface leakage along the sidewalls and reducing the V r as shown in Fig. 7(b).…”
Section: Influence Of Dielectric Layer On W Of Gan-msndmentioning
confidence: 99%
“…[29] And its value of 2 × 10 12 cm −2 is employed in this work. [30,31] Conversely, the electron accumulation region is formed near the trench surface due to the positive Q f at the SiO 2 /GaN interface, which is the main factor of increasing the surface leakage along the sidewalls and reducing the V r as shown in Fig. 7(b).…”
Section: Influence Of Dielectric Layer On W Of Gan-msndmentioning
confidence: 99%
“…We have previously reported that the improvement in the g m profile (the wider range of constant g m ) on InP-based HEMTs with a steam-annealed ultrathin-Al 2 O 3 gate dielectric (2 nm thick), due to a reduction in gate leakage current and an increase in forward breakdown voltage. 19) However, when using oxidant sources for ALD-Al 2 O 3 , the narrow band gap (∼3.4 eV) deficient indium oxide (InO x ) is generated in the surface-oxide of the In-based epitaxial layer, [20][21][22][23] thereby increasing the gate leakage current. 24) Thus, we developed inverted MOS-HEMTs with a surface-oxide-control (SOC) process that decreased the amount of InO x at the Al 2 O 3 /semiconductor interface.…”
Section: Introductionmentioning
confidence: 99%
“…[29] However, owing to its electron traps such as oxygen vacancies, deficient In 2 O 3 (InO x ) induces the current collapse in GaN HEMTs that use In-based barrier layers. [30][31][32][33] We previously proposed H 2 O vapor oxidation to decrease the amount of InO x in the surface-oxide by focusing on the thermal stability of the intermediate hydroxide and showed a decreased gate leakage current and current collapse in InAlN/GaN HEMTs using H 2 O vapor. [30,31] Alternatively, when using H 2 O vapor as an oxidant source for ALD-Al 2 O 3 (H 2 O vapor-Al 2 O 3 ), the density of the dielectric is lower than that obtained when O 2 plasma (O 2 plasma-Al 2 O 3 ) [34] DOI: 10.1002/pssa.202100638 Herein, Al 2 O 3 /InAlGaN/GaN metal-insulator-semiconductor high-electronmobility transistors (MIS-HEMTs) using H 2 O vapor pretreatment to decrease the amount of deficient indium oxide (InO x ) is successfully developed.…”
Section: Introductionmentioning
confidence: 99%